PENGARUH MOTIVASI KERJA,PENGEMBANGAN SUMBER DAYA MANUSIA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS KOPERASI DAN UMKM KABUPATEN PARIGI MOUTONG - Huzaemah, Huzaemah (Katalogis, 2019)
This Study aims to determine the influence of work motivation, human resource development and work discipline on employee’s performance at Cooperatives and Small and Medium Enterprise Office of Parigi Moutong Regency. Data was collected through quitionnaire. The result of the study shows that it is valid and reliable. Sample of the study was the entire of employees which amounted to 30 people. Sample is selected by using probability sampling method and then selcted through (validity test) and (reliability test) method. These tests used computer software of IBM SPSS statistical version 2012 program.